Development of Professional Competence of Future Physical Education Teachers Based on Innovative Approaches (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Relevance. This article examines the development of the professional competence of future physical culture teachers based on an innovative approach.Aim. The aim of the study is to determine the basic concepts for ensuring the educational process for the development of professional competence of future physical culture teachers on the basis of an innovative approach.Methods. In this article were used methods of abstraction and concretization, statistics, comparative analysis, work with documents and forecasting, questionnaires.Results. The types of competence, researches of scientists on the chosen topic are analyzed.Conclusion. Conclusions are given about the forms, methods and means for the development of professional competence of future physical culture teachers on the basis of an innovative approach.